MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMK MANSYAUL HUDA TEGALDLIMO BANYUWANGI - Ilham Nur Kholiq; Mohammad Syamsudin (Institut Agama Islam Darussalam Blokagung, 2021)
SMK Mansyaul Huda is a fast-paced school with two majors, namely TKR and TKJ. The purpose of this study was to find out how the management, quality of education and the factors supporting and inhibiting infrastructure facilities at SMK Mansyaul Huda. This study uses a description method with a qualitative approach. The research location is at SMK Mansyaul Huda. Data collection is through observation, interviews, and documentation. Research subjects: Principal,. Types and Sources of Data, namely Primary Data and Secondary Data, Data examination techniques using triangulation. Data analysis uses Data Reduction, Data Presentation, and Data Verification.The results are 1) Management of infrastructure from planning, implementation, evaluation and accountability has been implemented properly 2) Quality of education by optimizing MGMPAI. Holding UTS, daily tests, tutoring, remedials, UAS and procurement of teaching materials. 3) Supporting factors for cooperating with the school community, the fulfillment of media tools, teachers who are experts in their fields. constraining factor is limited funds.